Hubungan Aktivitas Belanja Online dengan Management Keuangan Pribadi di Kalangan Mahasiswa - Desnira Nulhakim; David Rizar Nugroho; Enden Darjatul Ulya; Mulyono Mulyono (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
This study aims to analyze the relationship between online shopping activities and personal financial management among university students in Indonesia. The background of this research lies in the increasing digitalization of daily consumption, which has encouraged students to engage more actively in e-commerce transactions. Using a quantitative correlational design, data were collected from 100 undergraduate students through an online questionnaire based on Likert-scale indicators. The independent variables consist of buyer characteristics (age, gender, and income sources) and online shopping activities (frequency, spending amount, and shopping motivation). Meanwhile, personal financial management is measured through financial planning and spending control. The findings show that students demonstrate very high levels of online shopping activity and acknowledge the strong influence of demographic factors on their consumption behavior. Descriptive analysis also indicates high scores for financial planning and spending control, although intensive online shopping remains a potential risk to financial stability. The implications of this study highlight the need to strengthen financial literacy among students to help them develop healthier budgeting habits and reduce impulsive buying driven by digital platforms. This research is expected to contribute to the understanding of digital consumer behavior and support the development of financial education programs for young adults.